If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying (x^{3}+ y^{5})(x^{3}+ -1y^{5}) = 0 Multiply (x^{3}+ y^{5}) * (x^{3}+ -1y^{5}) (x^{3}(x^{3}+ -1y^{5}) + y^{5}(x^{3}+ -1y^{5})) = 0 ((x^{3}* x^{3}+ -1y^{5}* x^{3}) + y^{5}(x^{3}+ -1y^{5})) = 0 Reorder the terms: ((-1x^{3}y^{5}+ x^{6}) + y^{5}(x^{3}+ -1y^{5})) = 0 ((-1x^{3}y^{5}+ x^{6}) + y^{5}(x^{3}+ -1y^{5})) = 0 (-1x^{3}y^{5}+ x^{6}+ (x^{3}* y^{5}+ -1y^{5}* y^{5})) = 0 (-1x^{3}y^{5}+ x^{6}+ (x^{3}y^{5}+ -1y^{10})) = 0 Reorder the terms: (-1x^{3}y^{5}+ x^{3}y^{5}+ x^{6}+ -1y^{10}) = 0 Combine like terms: -1x^{3}y^{5}+ x^{3}y^{5}= 0 (0 + x^{6}+ -1y^{10}) = 0 (x^{6}+ -1y^{10}) = 0 Solving x^{6}+ -1y^{10}= 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y^{10}' to each side of the equation. x^{6}+ -1y^{10}+ y^{10}= 0 + y^{10}Combine like terms: -1y^{10}+ y^{10}= 0 x^{6}+ 0 = 0 + y^{10}x^{6}= 0 + y^{10}Remove the zero: x^{6}= y^{10}Simplifying x^{6}= y^{10}Combine like terms: y^{10}+ -1y^{10}= 0 x^{6}+ -1y^{10}= 0 Factor a difference between two squares. (x^{3}+ y^{5})(x^{3}+ -1y^{5}) = 0## Subproblem 1

Set the factor '(x^{3}+ y^{5})' equal to zero and attempt to solve: Simplifying x^{3}+ y^{5}= 0 Solving x^{3}+ y^{5}= 0 Move all terms containing x to the left, all other terms to the right. Add '-1y^{5}' to each side of the equation. x^{3}+ y^{5}+ -1y^{5}= 0 + -1y^{5}Combine like terms: y^{5}+ -1y^{5}= 0 x^{3}+ 0 = 0 + -1y^{5}x^{3}= 0 + -1y^{5}Remove the zero: x^{3}= -1y^{5}Simplifying x^{3}= -1y^{5}The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.## Subproblem 2

Set the factor '(x^{3}+ -1y^{5})' equal to zero and attempt to solve: Simplifying x^{3}+ -1y^{5}= 0 Solving x^{3}+ -1y^{5}= 0 Move all terms containing x to the left, all other terms to the right. Add 'y^{5}' to each side of the equation. x^{3}+ -1y^{5}+ y^{5}= 0 + y^{5}Combine like terms: -1y^{5}+ y^{5}= 0 x^{3}+ 0 = 0 + y^{5}x^{3}= 0 + y^{5}Remove the zero: x^{3}= y^{5}Simplifying x^{3}= y^{5}The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

| 5x^2+11x+1=0 | | y^2-16y-4= | | y=5x^2-3x+5 | | 7x-28=2x^2-8x-3x+12 | | y=x^2+5x | | y=x^2+2x | | x^7-5x^5+x^2-5=0 | | 15x^2-8x-7=0 | | X^2+6x-27=0 | | 3x^2-6x+12=0 | | (4x^3-6x^2+5)-(8x^2+3x-6)= | | 11x^2-2x+9=0 | | 4x(2x^2-6x-5)= | | 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 | | 9x^2+21x+12=0 | | -2x^2+4x+12=0 | | 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 | | (8x^4+5x^3-5)-(5x^2-6x+4)= | | 2x^2+10x+12=0 | | (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= | | X^2-5x-48=0 | | X^2-12x+20=0 | | x^4-4x^3+5x^4-9x^3+2= | | (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= | | y=x^3+3x^2-9x-8 | | 4x^4+3x^2-1=0 | | kx^2+4x+(5-k)=0 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions